Morphometric Discriminant Analysis of isolated chondrichthyan scales for palaeoecological inferences: the Middle Triassic of the Iberian Chain (Spain) as a case of study - Ferrón, H.; Pla, C.; Martínez-Pérez, C.; Escudero-Mozo, M.J.; Botella, H. (Journal of Iberian Geology, 2014)
Palaeontological studies on exosqueletal disarticulated remains of chondrichthyans have focused on teeth and only less interest has been paid to scales due their limited taxonomic and systematic significance. However, classical works linking the morphology and the function of the squamation in extant sharks suggest that, despite their limited taxonomic value, the study of isolated scales can be a useful tool for palaeoenvironmental and palaeoecological inferences. Following this idea, we have analyzed the fossil record of shark scales from two Middle Triassic sections of the Iberian Chain (Spain), identifying different functional types by means of a morphometric discriminant analysis. From a total of 1136 isolated chondrichthyan scales, 25% were identified as abrasion resistant scales, 62% as drag reduction scales and 13% as scales of generalized functions. The elevated proportion of abrasion resistant scales suggests that this chondrichthyan palaeocommunity was highly dominated by benthic sharks that lived over a hard sea floor. However, one of the stratigraphical levels studied (He-20), presents statistically significant differences from the others, showing a lower percentage of abrasion resistant scales and a larger percentage of drag reduction scales. This level can be linked with storm episodes that could introduce remains of bentho-pelagic or pelagic forms in the inner platform.. Finally, partial correlation analysis between relative abundances of functional scale types and tooth-based taxa from the same sections provide positive correlation between teeth of Hybodus and Pseudodalatias and drag reduction scales, and teeth of Prolatodon and abrasion strength scales.